An exploratory study on the educational attainment of youth who have reached eighteen whilst in foster care in Ocean View, Cape Town - Siyawareva, Benson Tatenda (Department of Social Development, 2020)
The overall aim of the study was to explore educational attainment of youth who have reached eighteen whilst in foster care in Ocean View, Cape Town. A qualitative research design and a purposive sampling technique were adopted to recruit the participants. Furthermore, nonprobability sampling has been utilised to draw a purposive sampling. Semi-structured one-toone interviews were used in this study. The participants were males and females between the ages of eighteen and twenty years, who had reached eighteen whilst in foster care. Children in foster care associated their goals in life with educational attainment. The study revealed that the youth who turned eighteen whilst in foster care identified importance pertaining to education as the only way that could help themselves to get their desired jobs and achieve their educational goals in life. The study found that children in foster care appreciate social support and kindness they receive from their foster parents, which they considered as crucial in their lives because their biological parents could not provide for them. However, some of the participants expressed great concerns over the treatment they were receiving from their foster parents as a major setback in their lives, which could hinder them from achieving their education goals. The study also shows that the participants in the study encounter financial challenges such as not having money to access tertiary education similar to many children from an impoverished family backgrounds. The main recommendations are that there is a need for collaboration between the foster parents, social workers and the class teachers in offering social support to the participants who are in foster care.